Insights into a 429-million-year-old compound eye - Brigitte Schoenemann (Nature Portfolio, 2020)
Abstract In all arthropods the plesiomorphic (ancestral character state) kind of visual system commonly is considered to be the compound eye. Here we are able to show the excellently preserved internal structures of the compound eye of a 429 Mya old Silurian trilobite, Aulacopleura koninckii (Barrande, 1846). It shows the characteristic elements of a modern apposition eye, consisting of 8 (visible) receptor cells, a rhabdom, a thick lens, screening pigment (cells), and in contrast to a modern type, putatively just a very thin crystalline cone. Functionally the latter underlines the idea of a primarily calcitic character of the lens because of its high refractive properties. Perhaps the trilobite was translucent. We show that this Palaeozoic trilobite in principle was equipped with a fully modern type of visual system, a compound eye comparable to that of living bees, dragonflies and many diurnal crustaceans. It is an example of excellent preservation, and we hope that this manuscript will be a starting point for more research work on fossil evidence, and to develop a deeper understanding of the evolution of vision.